1989
DOI: 10.1128/aem.55.10.2723-2725.1989
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Trichloroethylene to Pseudomonas putida F1 Is Mediated by Toluene Dioxygenase

Abstract: Trichloroethylene was metabolically activated by toluene dioxygenase to produce toxic effects in Pseudomonas putida Fl. Cytotoxicity was indicated by growth inhibition and by the covalent modification of cellular molecules in P. putida Fl exposed to ['4C]trichloroethylene. With a toluene dioxygenase mutant, neither growth inhibition nor alkylation of intracellular molecules was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 20 publications
7
54
0
Order By: Relevance
“…M declines [3]. The same phenomenon has been observed in other microorganisms that degrade TCE [4]. It has been suggested that the short half-life of TCE-degradation activity is due to enzyme inactivation by toxic intermediates formed by TCE degradation [5].…”
Section: Introductionsupporting
confidence: 65%
“…M declines [3]. The same phenomenon has been observed in other microorganisms that degrade TCE [4]. It has been suggested that the short half-life of TCE-degradation activity is due to enzyme inactivation by toxic intermediates formed by TCE degradation [5].…”
Section: Introductionsupporting
confidence: 65%
“…It is well known that enzymatic transformation of certain compounds can result in deleterious metabolic effects.2.1S, 18,28,34,42 However, the distinct mechanisms of inhibition and inactivation have not been modeled entirely satisfactorily to date. Competition for the primary enzyme of interest has been noted p r e v i o u~l y ,~~ and models have been proposed in which enzyme inactivation is expressed in terms of decreases in "active biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Highest purity methane ( s 99.99%, Matheson) was used for cell growth. [1,[2][3][4][5][6][7][8][9][10][11][12][13][14] C]TCE (99.8%) was obtained from New England Nuclear. Milli-Q water from a Corning Millipore D2 system was used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Anaerobic biotransformation of TCE proceeds through reductive dechlorination and produces the toxic agents dichloroethylene (DCE) and vinyl chloride (VC) [4,5]. Several aerobic bacteria including toluene oxidizers [6,7], ammonia oxidizers [8,9] and methane oxidizers [101 7] have also been shown to degrade TCE, but without the production of DCE or VC, and therefore can be useful alternatives. Since methane is non-toxic and methano-trophs are ubiquitous in the environment [18], these bacteria have been extensively examined for TCE bioremediation.…”
Section: Introductionmentioning
confidence: 99%